Outcome-Based Education in the Age of Artificial IntelligenceA Thematic Tafsīr Analysis of Curricular Impacts in Islamic Higher Education - Lilis Fauziah Balgis; Syamsudin Ali Nasution; Novi Maryani (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Artificial Intelligence (AI) is increasingly reshaping Outcome-Based Education (OBE) by expanding opportunities for personalized learning, curriculum responsiveness, assessment efficiency, and student support. In Islamic higher education, however, the growing reliance on measurable outcomes and algorithmic processes raises concerns about whether moral, spiritual, relational, and holistic dimensions of learning may receive insufficient attention. This study examines the curricular implications of AI-driven OBE through the perspective of thematic Qur’anic exegesis (tafsīr mawḍū‘ī). Using a qualitative library research design, the study integrates a structured review of contemporary scholarly literature published primarily between 2022 and 2026 with a thematic analysis of relevant Qur’anic concepts and classical and contemporary exegetical sources. The analysis reveals that AI can enhance learning personalization and support the alignment of educational processes with intended outcomes, while also creating concerns related to algorithmic bias, data privacy, transparency, and human agency. These developments are interpreted through the interconnected concepts of ta‘līm, tarbiyah, and ta‘dīb, which emphasize intellectual development, holistic nurturing, and moral cultivation. The study further identifies maqāṣid al-sharī‘ah as a normative basis for evaluating and governing AI in ways that uphold human dignity, intellect, justice, welfare, and accountability. An integrative framework is consequently proposed to connect AI-OBE implementation, ethical governance, competency and character development, and continuous quality improvement. The study concludes that AI should remain an enabling educational instrument guided by human judgment and Islamic ethical principles rather than becoming the primary determinant of educational value.